Up-regulation of c-FLIPshort and reduction of activation-induced cell death in CD28-co-stimulated human T cells - Kirchhoff, Sabine; Li-Weber, Min; Krammer, Peter H. (European journal of immunology, 2000)
Efficient activation of antigen-specific T cells requires co-stimulatory signals provided e.g. by CD28. Re-exposure to antigen and CD28 co-stimulation reduces activation-induced cell death (AICD) and increases the number of T cells performing effector functions. AICD is mediated predominantly by CD95 (APO-1/Fas) and its cognate ligand (CD95L). In an in vitro model system, using human peripheral activated T cells, we demonstrate here that co-stimulation prevents CD95L expression. Moreover, we show that co-stimulation reduces the activity of the CD95 death-inducing signaling complex and procaspase-8 activation. In parallel, co-stimulation strongly increases expression of the short form of the FLICE-inhibitory protein c-FLIPshort and of Bcl-xL. These data provide important new insight into the molecular mechanisms of apoptosis resistance in co-stimulated T cells.
Gesehen am 26.04.2021
Im Titel ist der Ausdruck "short" tiefgestellt